Two and three-dimensional characterisation of localised corrosion affected by lack-of-fusion pores in 316L stainless steel produced by selective laser melting. (1st April 2020) - Laleh, Majid; Hughes, Anthony E.; Yang, Sam; Li, Jianli; Xu, Wei; Gibson, Ian; Tan, Mike Y.
Highlights: Porosity in SLM-produced 316 L SS determines the susceptibility to localised corrosion. Lack-of-fusion pores were found to be extremely susceptible to localised corrosion. 3 dimensional CT has been used to show localised corrosion development at the site of LOF pores. Abstract: Localised corrosion of 316 L stainless steel (316 L SS) produced by selective laser melting (SLM) was investigated by two and three-dimensional techniques. It was revealed that porosity, which inevitably exists in the SLM-produced parts, is a critical factor determining the susceptibility to localised corrosion. Specimens containing lack-of-fusion (LOF) pores were found to be extremely susceptible to localised corrosion, as indicated by their lower breakdown potentials measured in polarisation tests. Computed tomography (CT) analysis, capable of linking the microstructure and corrosion propagation paths in three dimensions, showed the development of localised corrosion at the sites of LOF pores upon exposure to ferric chloride solution.